Biochemical studies among different isolates of Magnaporthe grisea (Anamorh-Pyricularia grisea) from different hosts - R.A. SINGH, ARUN KUMAR and (Indian Phytopathology, 2002)
Lipids and fatty acids pattern of three isolates of Pyricularia grisea Sacc. isolated from rice, finger millet and pearl millet have been analyzed. The differences in lipids and fatty acids patterns showed that rice and finger millet isolates are closer to each other as compared to pearl millet isolate of the fungus.